Histological and Physiological Study of Hyaluronic Acid Filler (Neuramis) in Laboratory Rats: Studi Histologis dan Fisiologis Filler Asam Hyaluronic (Neuramis) pada Tikus Laboratorium - Afrah Ali Abdulameer; Satar Abood Faris (Universitas Muhammadiyah Sidoarjo, 2024)
Hyaluronic acid (HA) dermal fillers, derived from animal or non-animal sources, vary in physical and chemical properties, with numerous clinical trials assessing their effectiveness. This study examined the effects of Neuramis Volume Lidocaine on experimental animals over five durations (2, 4, 9, 10, and 13 weeks) via subcutaneous injections of 0.1 ml. Results showed a significant reduction in red blood cells, hemoglobin, and platelets after two weeks, which normalized by weeks 10 and 13. White blood cells and neutrophils significantly increased at two weeks but stabilized thereafter, while lymphocyte levels showed no significant long-term changes. Monocytes significantly decreased at two weeks but normalized by weeks 9-13. Scanning electron microscopy (SEM) revealed skin changes, including collagen bundle alterations and surface perforations. By week 10, the skin showed well-defined collagen structures and dense papillae, while earlier weeks exhibited more pronounced damage. These findings highlight HA fillers’ potential short-term physiological and histological impacts, which diminished over time. Highlights: Hyaluronic acid fillers vary in sources, properties, and clinical effectiveness. Blood parameters altered early; histological changes observed, diminishing over time. Fillers cause temporary physiological and histological issues, improving with duration. Keywords: Hyaluronic acid, Histological study, Physiological study, Laboratory rats